Essentials of Teaching and Integrating Visual and Media Literacy Visualizing Learning - Baylen, Danilo M.; D'Alba, Adriana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Core concepts and novel applications of visual and media literacy take center stage in this comprehensive volume. Dedicated equally to contexts for framing visual knowledge, models for integrating media into class work, and proven strategies for promoting visual and media literacy from kindergarten through college, it offers a complete teaching framework suited to an increasingly digital world. Coverage clearly details the range of visual materials adaptable to the classroom and the relationships between media literacy and student engagement, critical thinking, problem solving, and creativity. Here are opportunities for learners not only to enhance their current use of media, but also to acquire skills that will serve them throughout their lives.   Among the topics covered:   Reinforcing multiliteracies through design activities. Visual communication and culture: design education for a globalized world. Cameras in the classroom: photography’s pedagogical potential. Multi-modal composition in teacher education: from consumers to producers. Teaching visual and media literacy skills through media production technology. Teaching visual literacy: pedagogy, design and implementation, tools and techniques.   Essentials of Teaching and Integrating Visual and Media Literacy paints the future of education in vivid perspective for practitioners and professionals across disciplines.  .
Visual and Media Literacy Defined.- Tools for Visual-Based Learning.- Applications of Visual and Media Literacy Teaching -- Teaching Visual and Media Literacy across the K-12 Curriculum -- Teaching Visual and Media Literacy in Higher Education.- Teaching Visual and Media Literacy to Support Diverse Learners.- Rethinking Learning and Teaching in a Visual-Rich World.- Index.
Keywords: Educational technology; Learning; Instruction; Educational Technology; Learning & Instruction